CHILDFREE IN THE QUR’AN: Reinterpretation of Al-Naḥl Verse 72 with Ma’nā Cum Maghzā Approach - Ma'isyatusy Syarifah; Hudzaifah Achmad Qotadah (AL-TAHRIR, 2022)
Abstract: Childfree can be interpreted as the view of a husband and wife who decide not to have children, which is often considered contrary to the one purpose of marriage in the Islamic perspective to have children. It is important to explain how the Qur'an respons to the polemic of childfree, while the Qur'an itself strongly echoes the urgency of having children. This article is qualitative descriptive research with a socio-religious approach and uses the hermeneutic theory of ma'na-cum-maghza as an analytical tool, this paper aims to analyze Surah Al-Naḥl 72 related to how the Qur'an talks about the pros and cons of childfree. This is done to prove that the Qur'an ṣaḥīẖ li kulli zamān wa makān (relevant for every time and place) is used as a reference in solving contemporary problems. This research finds that Surah Al-Naḥl verse 72 it is clearly explained that one of the purposes of marriage is to have children, while the childfree decision contradicts the absolute purpose of marriage in the Qur'an, but in some conditions, if not possible to have children, such as a disease that endangers the mother's life when pregnant and giving birth to a child, it is permissible to decide to be childfree, but if it is only a matter of parents worrying about not being able to educate and raise their child properly, it is prohibited because in Al-Naḥl verse 72 Allah will also guarantee fortune for the children in a family. Keywords: Al-Qur'an, Childfree, Ma'na Cum Maghzaالملخص: عدم وجود الأطفال (childfree ) باتفاق بين الزوج والزوجة يعتبر في كثير من الأحيان مخالفاً لهدف الزواج. فكذلك اهتم هذا البحث في نظر سورة النحل اية ٧٢ لحصول الاجبابة في مسآلة childfree. هذا المقال عبارة عن بحث وصفي نوعي اعتمادا بمنهج اجتماعي ديني بحيث يستخدم نظرية التأويل ma'na cum maghza. وجد هذا البحث أن سورة النحل الآية 72 توضح بوضوح أن أحد مقاصد الزواج هو الإنجاب ،بينما قرار الخلو من الأطفال يتعارض مع الهدف المطلق للزواج في القرآن ، لكن في بعض الحالات إن لم يكن لحصول الأولاد بسبب من الاسباب الشرعية كمثل المرض الذي يعرض حياة الأم فيجوز اتخاذ قرار بفعل childfree.الكلمات المفتاحية:  القزآن، اية، Childfree، Ma'na Cum Maghza                                        Abstrak: Childfree merupakan salah satu fenomena terbaru dalam kehidupan masyarakat modern saat ini. Childfree dimaksudkan sebagai keputusan seorang suami istri untuk tidak memiliki seorang anak. Tentu saja fenomena ini mendapatkan beragama reaksi dari berbagai komunitas muslim khususya sebab dianggap bertentangan dengan salah satu tujuan pernikahan yaitu melangsungkan keturunan. Karena itu, artikel ini merupakan penelitian deskriptif kualitatif dengan pendekatan sosio-religius dan menggunakan teori hermeneutic ma'na-cum-maghza sebagai alat analisis. Makalah ini bertujuan untuk menganalisis surah al-Naḥl 72 terkait dengan bagaimana Al-Qur'an berbicara tentang pro dan kontra persoalan childfree. Hal ini dilakukan untuk membuktikan bahwa Al-Qur'an saḥīẖ li kulli zamān wa makān untuk digunakan sebagai referensi dalam memecahkan masalah kontemporer. Hasil penelitian menunjukkan bahwa dalam surah al-Naḥl ayat 72, melestarikan keturunan (memiliki anak) merupakan fitrah manusia dari adanya pernikahan, sedangkan praktek childfree bertentangan dengan tujuan asal pernikahan. Akan tetapi dalam beberapa kondisi tertentu dan terdapat alasan-alasan yang syar’i seperti penyakit yang membahayakan nyawa ibu dan sebagainya, maka keputusan childfree dapat dibenarkan.Kata kunci: Al-Qur'an, Childfree, Ma'na Cum Maghza